Time-resolved EPR investigation of oxygen and temperature effects on synthetic eumelanin. Issue 3 (2010) - Conti, Fosca; Panzella, Lucia; Napolitano, Alessandra; d᾽Ischia, Marco; Toffoletti, Antonio
Abstract : Synthetic eumelanin produced using 5, 6-dihydroxyindole-2-carboxylic acid as precursor and H2 O2 /horseradish peroxidase as oxidative reagent, in form of dry powder, has been investigated under photoexcitation by TR-EPR spectroscopy. The formation of spin polarized radical pairs from triplet excited states of melanin has been observed both in absence and in presence of oxygen and has been followed as a function of the temperature in the range 140–290 K. The triplet mechanism explains the observed polarization pattern in net emission. In the presence of oxygen new radical pairs are formed by interaction of melanin with molecular oxygen.